Pagan Christs: studies in comparative hierology - Robertson, John M. (Watts & Co., 1911)
Preface. -- Introduction -- pt. I. The rationale of religion. -- pt. II. Secondary God-making. -- pt. III. Mithraism. -- pt. IV. The religions of ancient America.